Measuring thermal conductivity via basic home equipment - Erol, Mustafa; Kuzucu, Muhammed Emre (Universitas PGRI Kanjuruhan Malang, 2022)
This work reports a trouble-free alternative measuring approach for instructing the puzzling concept of thermal conductivity. In order to accomplish the task, a basic daily used home equipment is employed together with a mathematical modelling approach. Specifically, a simple approach to measure the thermal conductivity coefficient is described and temperature dependence of the thermal conductivity is mathematically modelled. Developed method is interesting in the sense that the experimental equipment is very practical and minimal costing, hence the approach offers physics educators fresh teaching routes and opportunities to clarify the puzzling concept of thermal conductivity and related concepts.